Redução do sódio em queijo minas padrão: efeito nas características físico-químicas e no perfil de textura - Hachiya, Jefferson Sussumu de Aguiar (2015)
Sodium is an essential component in the feed, however, the excessive use is associated with health problems such as hypertension, reduce calcium absorption, the renal problems, among others. The cheeses have been identified as one of the products with high in sodium, so based on this context the aim of this study was to evaluate the effect of partial substitution of sodium for potassium chloride on the physicochemical characteristics and texture of the cheese type Minas Standard. The preparation of Mines standard cheeses occurred with replacement of sodium by potassium chloride in the proportions of 100% NaCl (control), 80% NaCl 20% KCl + (T1) + 60% NaCl 40% KCl (T2 ) + 40% NaCl 60% KCl (T3) and 20% NaCl 80% KCl + (T4). The physicochemical evaluation consisted in determining the moisture content, protein, fat, ash and chlorides at 0 and 30 days of aging at 12ºC. The pH, titratable acidity, length and depth index maturation were assessed at 0, 7, 15 and 30 days of aging at the same temperature. The texture profile analysis was to assess the firmness, elasticity, adhesiveness, cohesiveness and chewiness. This study found that the increase in the proportion of potassium had a significant effect (p <0.05) in moisture, protein and chlorides. The substitution of sodium for potassium increased the moisture content and reduced the protein content. The cheese chloride levels were less than 0.6%, ranging between 0.319 and 0.594%, where the treatments with higher potassium concentrations showed statistical difference (p <0.05) than the other. The replacement of the salts had no significant effect on fat and ash in all treatments. The water activity decreased by replacing sodium by potassium. The sodium content between treatments varied between 53.85 and 157.36 g mg.100-1, while the potassium content were 120.72 to 364.67 g mg.100-1 to rank treatments with larger potassium levels as very low in sodium. The replacement of sodium by potassium did not significantly affect the pH, extent and depth index maturation of all treatments. On the other hand, there was a significant increase in titratable acidity in treatments with lower levels of sodium. When evaluating the adhesion parameters, elasticity, cohesiveness and chewiness of the cheese were not statistically different (p> 0.05) between treatments, and the sodium for potassium replacement negatively affected the strength (p <0.05) cheese type standard mines. Therefore, the substitution of potassium for less than 40% was feasible for production Mines standard cheeses with little effect on the proximal composition and physico-chemical texture.